English as a neutral language in the colombian national standards: a constituent of dominance in english language education (2009)
This article attempts to problematize the way the English language is used in official documents. We will focus on the “Estándares Básicos de Competencias en Lenguas Extranjeras: Inglés” (Basic Standards of Competences in Foreign Languages: English), a handbook issued by the Colombian Ministry of Education. We deem it as a vehicle used to spread a hegemonic and ideological influence and to alienate teachers’ beliefs and practices within English language education. To be concise, here we discuss only neutrality as one broad category that emerges in our close examination of how the English language is constructed within the handbook. In this paper, we construct our main points around three forms of neutrality: prescription, denotation, and uniformity. Key words: English as a neutral language, English language education, foreign language standards, critical discourse analysis, symbolic power, language policies Este artículo intenta problematizar la manera como el idioma inglés es construido en documentos oficiales. Concretamente, nos centramos en los “Estándares Básicos de Competencias en Lenguas Extranjeras: Inglés”, una cartilla emitida por el Ministerio de Educación colombiano. Consideramos este manual un vehículo usado para difundir la influencia hegemónica e ideológica y para alienar las creencias y prácticas de maestros dentro del campo de la educación de la lengua inglesa. Aquí, por razones de espacio, sólo se discute la neutralidad como una gran categoría que surge de un examen detallado de cómo el idioma inglés es construido dentro de la cartilla. En este escrito, presentamos nuestros puntos principales alrededor de tres formas de neutralidad: prescripción, denotación y uniformidad. Palabras clave: Inglés como un idioma neutro, educación del idioma inglés, estándares de idiomas extranjeros, análisis crítico del discurso, poder simbólico, políticas lingüísticas